THE ROLE AND STRATEGY OF DIGITAL TECHNOLOGY IN IMPROVING THE ARABIC LANGUAGE LEARNING PROCESS - Susiawati, Iis; Mardani, Dadan; Alhaq, Muhammad Faiz (HUNAFA Jurnal Studia Islamika, 2024)
Digital transformation has brought significant changes to various aspects of life, including the field of education. However, there is still a gap in the literature regarding the role and strategies of digital technology specifically in Arabic language learning. This article aims to analyze the existing literature on the role and strategies of digital technology in enhancing the process of learning the Arabic language. Through a literature review method, this article explores various previous studies and research discussing the implementation of digital technology in Arabic language learning and evaluates its impact on the effectiveness of learning. The analysis shows that the use of digital technology, such as learning applications, e-learning platforms, and interactive tools, can increase students' motivation, engagement, and learning outcomes in Arabic language learning. However, there are also challenges that need to be addressed, such as the lack of technological infrastructure and digital skills among educators. Recommendations for strategies to optimize the use of digital technology in Arabic language learning in the future, including the development of digital-based curricula, training and professional development for educators, technological infrastructure and accessibility, development of interactive learning resources, collaboration between schools and technology providers, regular evaluation and monitoring, and enhancement of students' digital skills.